2013
DOI: 10.1002/grl.50825
|View full text |Cite
|
Sign up to set email alerts
|

Subaqueous melting of Store Glacier, west Greenland from three‐dimensional, high‐resolution numerical modeling and ocean observations

Abstract: [1] We present three-dimensional, high-resolution simulations of ice melting at the calving face of Store Glacier, a tidewater glacier in West Greenland, using the Massachusetts Institute of Technology general circulation model. We compare the simulated ice melt with an estimate derived from oceanographic data. The simulations show turbulent upwelling and spreading of the freshwater-laden plume along the ice face and the vigorous melting of ice at rates of meters per day. The simulated August 2010 melt rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
308
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(335 citation statements)
references
References 22 publications
26
308
1
Order By: Relevance
“…Turbidity measurements within and just outside of the surface plume (visually defined by the contrast in water colour), indicate that PluW sinks below the pycnocline of the SW after attaining the surface (Fig. 7), an observation that is in agreement with plume modelling at Store (Xu et al, 2013).…”
Section: Turbidity Analysis and Plume Observationsupporting
confidence: 78%
See 2 more Smart Citations
“…Turbidity measurements within and just outside of the surface plume (visually defined by the contrast in water colour), indicate that PluW sinks below the pycnocline of the SW after attaining the surface (Fig. 7), an observation that is in agreement with plume modelling at Store (Xu et al, 2013).…”
Section: Turbidity Analysis and Plume Observationsupporting
confidence: 78%
“…To date, several processes of interaction between fjord water and tidewater calving fronts have been observed, modelled and/or speculated upon including forced convection caused by buoyant subglacial fresh water (SgFW) discharged at depth and entraining AW as it rises (Jenkins, 2011;Mugford and Dowdeswell, 2011;Salcedo-Castro et al, 2011;Sciascia et al, 2013;Sole et al, 2012;Xu et al, 2012Xu et al, , 2013 as well as wind stress and tide-driven fjord circulation Sole et al, 2012;Straneo et al, 2010;Sutherland and Straneo, 2012). Furthermore, it is emerging that circulation in Greenland's deep fjords is more complex than the single convective cell (estuarine-like) circulation model that has been assumed previously in energymass balance calculations (Motyka et al, 2003;Rignot et al, 2010).…”
Section: N Chauché Et Al: Ice-ocean Interaction and Calving Front Mmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct effect of changes in temperature and salinity on the melt equations are well tested. Past studies using uniform ambient temperature and salinity conditions have found a linear relationship between increases in ambient fjord temperatures and melt rates, with the slope of the relationship dependent upon the discharge volume (P. R. Jenkins, 2011;Xu et al, 2013). Salinity, on the other hand, has been shown to have a negligible effect on melt rates (D. M. .…”
Section: Plume Model and Undercuttingmentioning
confidence: 99%
“…At the front of marine terminating glaciers, freshwater plumes are generated by subglacial discharge and submarine melting. The presence of multiple plumes may affect glacial melting (Xu et al 2013;Kimura et al 2014) through the modified entrainment in the interacting plumes.…”
Section: Introductionmentioning
confidence: 99%